El Kitāb Mīzān al-Ṭabīb de Ibn al-Bayṭār. Descripción del unico manuscrito conservado y contenido de la obra - Cabo-González, Ana M. (Folia Orientalia, 2026)
The pharmacologist of al-Andalus, born in Malaga and died in Damascus, Ibn al-Bayṭār (576/1180 or 583/1187–646/1248) composed a dozen works among which we must highlight: The Kitāb Mīzān al-Ṭabīb. The work presented here studies the only manuscript of this work that has been preserved, number 351 or Vet. 58 of the Universitetsbibliotek of Uppsala (Sweden) and describes the content of the same, a medical-pharmacological dissertation, divided into eighty chapters, each of which is dedicated to one or more diseases, going through all the organs of the body, starting with the head and ending with the feet.